Forgotten accounts of tropical cyclones making landfall in Tanzania. (14th March 2021) - Msemo, Hellen E.; Finney, Declan L.; Mbuya, Samwel I.
Abstract : Landfalling tropical cyclones are essentially unheard of in Tanzania. It has been suggested that Cyclone Kenneth, which occurred in 2019, was the first tropical cyclone to make landfall in Tanzania. This paper brings to light tropical cyclones that made landfall in Tanzania in 1872 and 1952. We draw on eyewitness accounts and meteorological observations to raise the profile of these seemingly forgotten tropical cyclones, which devastated lives and economic activities. The severe societal impacts, and potential link to climate change, of landfalling tropical cyclones in Tanzania encourages further investigation into the drivers of tropical cyclones in the southwest Indian Ocean. Abstract : The tracks of the Zanzibar and Lindi tropical cyclones on April 1872 and 1952, respectively. The approximate landfall position of cyclone Kenneth is also noted as 12°S to highlight that this occurred much further south than the two historical cyclones presented here.